Differences in Imaging Characteristics of HPV-Positive and HPV-Negative Oropharyngeal Cancers: A Blinded Matched-Pair Analysis - Cantrell, S.C.; Peck, B.W.; Li, G.; Wei, Q.; Sturgis, E.M.; Ginsberg, L.E. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: Human papillomavirus–positive oropharyngeal cancers typically have younger age of onset, limited tobacco exposure, and more favorable prognosis than HPV-negative oropharyngeal cancers. We assessed whether HPV-positive and HPV-negative oropharyngeal cancers have consistent differences in pretreatment imaging characteristics. MATERIALS AND METHODS: A retrospective review of 136 pretreatment CT examinations of paired HPV-positive and HPV-negative oropharyngeal cancers matched for T stage, tumor subsite, and smoking status was performed with the reviewing radiologist blinded to HPV status and clinical stage. Demographic/clinical characteristics and imaging characteristics of primary lesions and metastatic nodal disease were compared by use of Fisher exact testing. The McNemar χ2 test was used for the matched-pair analysis. RESULTS: By imaging, HPV-negative tumors were more likely to demonstrate invasion of adjacent muscle (26% versus 6%, P = .013). HPV-positive primary tumors were more likely to be enhancing and exophytic with well-defined borders, whereas HPV-negative primary tumors were more likely to be isoattenuated and demonstrate ill-defined borders, though these results were not statistically significant. HPV-positive tumors were more likely to demonstrate cystic nodal metastases than HPV-negative tumors (36% versus 9%, P = .002). CONCLUSIONS: In this matched and blinded analysis of the imaging differences between HPV-positive and HPV-negative oropharyngeal cancers, HPV-positive carcinomas often had primary lesions with well-defined borders and cystic nodal metastases, whereas HPV-negative primaries more often had poorly defined borders and invasion of adjacent muscle. HPVhuman papillomavirusSCCOPsquamous cell carcinomas of the oropharynxEGFRepidermal growth factor